1994
DOI: 10.1111/j.1399-3054.1994.tb02531.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall‐bound trans‐ and cis‐ferulic acids in growing maize roots

Abstract: E. 1994. Cell wall-bound trans-and cis-ferulic acids in growing maize roots -Physiol. Plant. 90; 734-738.The levels of ceil wall-bound trans-and ci's-ferulic acids in roots of dark grown Zea mays cv.LGl 1 plants were measured. They were quantified after alkaline hydrolysis of purified cell walls by reversed phase HPLC using fran.!-cinnamic acid as internal standard. The total amount of ferulic acid (trans-and cH-feruilc acid) in the root ba.se was 3-4 times higher than in the root tip. Cu-ferulic acid represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Cell wall-bound phenolics were extracted according to the method described by [17] with slight modifications. Briefly, 0.2 g DW of each pooled hypocotyl segment tissue was crushed in liquid nitrogen, then extracted with methanol/distilled water (80/20, v/v) and absolute ethanol consecutively, and finally centrifuged at 930 × g for 10 min.…”
Section: Extraction and Analysis Of Cw-bound Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell wall-bound phenolics were extracted according to the method described by [17] with slight modifications. Briefly, 0.2 g DW of each pooled hypocotyl segment tissue was crushed in liquid nitrogen, then extracted with methanol/distilled water (80/20, v/v) and absolute ethanol consecutively, and finally centrifuged at 930 × g for 10 min.…”
Section: Extraction and Analysis Of Cw-bound Phenolic Compoundsmentioning
confidence: 99%
“…Precisely how CW components and their intermolecular interactions are changed to allow CW stiffening during growth cessation is not completely known [17]. Azospirillum inoculation induced higher CW elasticity a biophysical indication of CW induced differences during plant cell elongation [3].…”
Section: Introductionmentioning
confidence: 99%
“…The trans-to-cis conversion of CA is able to occur both in vitro under light (Kahnt 1967) and in dark-grown root tissues (Locher et al 1994). However, information regarding the regulatory effects of cis-CA on PAL enzymatic activity remains scarce.…”
mentioning
confidence: 99%
“…However, information regarding the regulatory effects of cis-CA on PAL enzymatic activity remains scarce. Cis-cinnamic acid, like cis-p-coumaric acid, cis-ferulic acid, and ciscaffeic acid (Haskins et al 1964;Ohashi et al 1987;Braun and Tevini 1993;Locher et al 1994;Rasmussen and Rudolph 1997;Wu et al 2001), has been found to be naturally occurring (Yin et al 2003). The biological activities of cis-CA have also been demonstrated in plants (Veldstra 1953;Yang et al 1999).…”
mentioning
confidence: 99%
“…Другим возможным объяснением этого является модификация состава и свойств клеточной стенки вследствие присоединения феруловой кислоты к полисахаридным остаткам. В литературе в последнее время появились данные об участии фенольных кислот клеточной стенки в регуляции способности клетки к растяжению и формированию агрегатов [7,8 ]. Наши результаты свидетельствуют о ключевой роли этих соединений в процессах регенерации в каллусных культурах.…”
unclassified